Pelatihan Sadar Wisata Untuk Pengembangan Wisata Berbasis Masyarakat (Community Based Tourism) Di Desa Lubuk Beringin Kecamatan Batin III Ulu Kabupaten Bungo - Hendriyaldi; Erwita Dewi; Rike Setiawati; Erida; Ovie Yanti (WIDA Publishing, 2022)
Lubuk Beringin Village is one of the villages in Bungo Regency which is a village with enormous natural and cultural tourism potential. In addition to carrying out activities as farmers, the village community also develops local wisdom such as a prohibition to take fish in the river basin according to village custom, a prohibition on using tuba, poison centers, long trawls, and other chemicals to take fish in rivers, a prohibition on picking durian fruit if not ripe or fall alone in large quantities. This local wisdom is the main attraction for Lubuk Beringin Village and has become a tourist destination. Based on the results of interviews with Lubuk Beringin village officials during the preliminary survey, the main problems encountered in managing the Lubuk Beringin tourist destination are 1) Public awareness of the importance of tourism to support the village economy is still very low. 2) Community understanding of Sapta Pesona and tourist villages is still very low. The method used in PPM activities is through face-to-face meetings with the community and participation or known as the active participation lecture method of PPM partners. It is hoped that the implementation of this community service activity can overcome the problems that exist in Lubuk Beringin Village, Bathin III Ulu District, Bungo Regency. This activity was carried out on October 15 2022 at the Lubuk Beringin Village Hall. The output of this community service activity is the understanding of partners, namely BUMDes management, to be able to develop the tourism potential of Lubuk Beringin, publication in journals with ISSN.